2021
DOI: 10.1590/1678-7757-2021-0296
|View full text |Cite
|
Sign up to set email alerts
|

Optimal culture conditions for neurosphere formation and neuronal differentiation from human dental pulp stem cells

Abstract: Objectives: Human dental pulp stem cells (DPSCs) have been used to regenerate damaged nervous tissues. However, the methods of committing DPSCs into neural stem/progenitor cells (NSPCs) or neurospheres are highly diverse, resulting in many neuronal differentiation outcomes. This study aims to validate an optimal protocol for inducing DPSCs into neurospheres and neurons. Methodology: After isolation and characterization of mesenchymal stem cell identity, DPSCs were cultured in a NSPC induction medium and cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Differently from the method described by Duval (Duval et al, 2002) and Scemes (Scemes et al, 2003), neural stem cell subculture was optimized by dissociating neurospheres with Accutase Cell Dissociation Reagent (Thermo, Waltham, MA, USA) for 15 min at room temperature (RT), followed by addition of the culture medium to halt enzymatic activity. The use of Accutase reagent enhances the dissociation of neurospheres into single cells and promotes neurosphere reformation, as evidenced by previous studies (Diana et al, 2021;Gonmanee et al, 2021;Panchision et al, 2007). Each neurosphere preparation was cultured for a maximum of 1 month, equivalent to four cell passages.…”
Section: Neurosphere Culture Preparationmentioning
confidence: 99%
“…Differently from the method described by Duval (Duval et al, 2002) and Scemes (Scemes et al, 2003), neural stem cell subculture was optimized by dissociating neurospheres with Accutase Cell Dissociation Reagent (Thermo, Waltham, MA, USA) for 15 min at room temperature (RT), followed by addition of the culture medium to halt enzymatic activity. The use of Accutase reagent enhances the dissociation of neurospheres into single cells and promotes neurosphere reformation, as evidenced by previous studies (Diana et al, 2021;Gonmanee et al, 2021;Panchision et al, 2007). Each neurosphere preparation was cultured for a maximum of 1 month, equivalent to four cell passages.…”
Section: Neurosphere Culture Preparationmentioning
confidence: 99%
“…Indeed, there are many differences between the different protocols, some subtle and others more obvious [ 145 , 146 ]. For example, besides the adherent growth of cells, also non-adherent conditions can be applied for the formation of neurospheres that will further differentiate into neuron-like cells [ 147 , 148 ]. There are even some published comparisons between different neurodifferentiation conditions, but more consistent data and a higher number of studies remain mandatory for more robust conclusions to be drawn.…”
Section: A Hypothetical Alternative Approach To Model Mucopolysacchar...mentioning
confidence: 99%
“…Several studies reported that FGF/FGFR signaling also promotes neural differentiation in hDPSCs. In the presence of bFGF, increased hDPSC neurosphere size, neural morphology, and neurogenic marker upregulation were observed (Gonmanee et al, 2021 ; Li et al, 2019a ; Nagashima et al, 2017 ; Osathanon et al, 2011 ). FGF stimulation supplemented with RA and EGF could not differentiate hDPSCs into subtype-specific neurons, but they were able to induce crucial morphological changes, which led to the functional activation of differentiated neurons by demonstrating their ability to respond directly to their surrounding environment (Arthur et al, 2008 ).…”
Section: Neural Differentiationmentioning
confidence: 99%
“…Several protocols have been published to optimize the culture conditions of serum-free differentiated hDPSCs (Madanagopal et al, 2020 ; Sonoda et al, 2022 ; Zhang et al, 2017 ). Serum-free approaches are also applied to culture hDPSCs in spheroids, which may act as microniches providing a better culture environment to differentiate DPSCs (Bonnamain et al, 2013 ; Gonmanee et al, 2021 ). In comparison with adherent culture conditions, hDPSC spheroids show significant differences in neural gene expression, maturity, and proliferation potential (Gervois et al, 2015 ; Luzuriaga et al, 2019a ; Xiao and Tsutsui, 2013 ).…”
Section: Neural Differentiationmentioning
confidence: 99%